2019
DOI: 10.3390/agriculture9090195
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Energy Metabolism, Growth, and Meat Quality in Beef Cattle

Abstract: World meat production must increase substantially to support current projections in population growth over the next 30 years. However, maximizing product quality remains a focus for many in the meat industry, as incremental increases in product quality often signal potential increases in segment profitability. Moreover, increases in meat quality also address concerns raised by an ever-growing affluent society demanding greater eating satisfaction. Production strategies and valued endpoints differ worldwide, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 86 publications
(96 reference statements)
1
40
0
4
Order By: Relevance
“…The increase in demand for animal products due to the growing world population has been an ongoing challenge for the animal production sector worldwide [1]. Tremendous progress has been achieved over the past five decades in this regard, mainly due to improvements in genetic selection, health status, nutrition, and the use of antibiotics and growth promotants [2].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in demand for animal products due to the growing world population has been an ongoing challenge for the animal production sector worldwide [1]. Tremendous progress has been achieved over the past five decades in this regard, mainly due to improvements in genetic selection, health status, nutrition, and the use of antibiotics and growth promotants [2].…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of type I and type II A fibers in LT are higher than those in LL, the proportion of type II B fiber in LL is higher than that in LT ( 46 ). However, oxidative fibers (I and IIA) are known to have a decreased rate in the extent of postmortem pH decline and lightness and inherently have an increase in redness due to a higher myoglobin concentration, thus resulting in darker meat when compared to glycolytic muscles (type II B) ( 47 ). In this way, the LT muscle is expected to be darker than the LL muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation and differentiation of myoblasts were already associated with important economical traits in broiler chicken, including meat quality ( Nihashi et al, 2019 ). A study measuring the muscle fiber diameters observed a positive correlation and participation of this phenotype in the breast weight and percentage in chickens ( Koomkrong et al, 2015 ), also the fiber size, number, and composition are important traits related with meat quality ( Lefaucheur, 2010 ; Wicks et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%